Promovendo o interesse pela aprendizagem histórica dos alunos do ensino médio : a história do Teatro São João da Bahia (1812-1923) como elemento mediador - Nascimento, Lídia Ramos do (2023)
The dissertation research in History Teaching presents a discussion on the promotion of interest in the historical learning of high school students from the history of the São João da Bahia Theater (1812-1923), as a mediating element and object of investigation for a greater deepening in the study of local history, memory, and identity in the field of studies on cultural heritage in Salvador. Faced with the situation of demotivation before and during the Covid19 pandemic (2020-2021), I was concerned about the following question: "How to increase the interest of students in the discipline History in High School?" As specific objectives of the work, I listed: 1. To diagnose the level of knowledge of the students of the Rotary State College, about the urban history of Salvador and its theaters; 2. Identify and select episodes from the history of Teatro São João, Bahia, related to local history; 3. Construct narratives about the São João da Bahia Theater that explain and motivate its study from the conception of cultural heritage; 4. Elaborate didactic sequences with the use of facts from the history of the São João da Bahia Theater; 5. Apply the online Workshop on the São João Theater, in order to enhance the students' sense of belonging to the place where they live and thus expand the value of historical learning in their lives; 6. Evaluate the pedagogical results of the application (difficulties and advances); 7. Create a Heritage Education Manual for the application of the Workshop on the São João Theater. The theoretical guidance was given by reading authors such as Silio Boccanera, Saas and Liba, Rusen, Maria Auxiliadora Schmidt and Cainelli, Paul Ricoeur, Áurea Pinheiro, Sandra Pelegrini, Jacqueline Zarbato and Janaina Mello, among others. The methodology of this work was divided into two strands, in view of its theoretical and practical conception. Bibliographic data were collected in several databases, submitted to analytical procedures according to Bardin (2011). Qualitative-quantitative methodological procedures were adopted based on structured questionnaires applied to high school students and analyzed in their statistical data. In the practical part dialogical planning, the didactic sequences with the selection of the imagery material, audiovisual and apply the activities of Heritage Education in the format of an online Workshop, via Google Meet platform, to the students of the 2nd year of High School, of the Rotary State College, Salvador – BA. As products, a Manual of Heritage Education was presented with a script of replication of this for teachers of Basic Education who so wish to do so, a website and a Logbook of the activities carried out.